Double Diffusion As a Driver of Turbulence in the Stratified Boundary Layer Beneath George VI Ice Shelf. Issue 5 (4th March 2022) - Middleton, L.; Davis, P. E. D.; Taylor, J. R.; Nicholls, K. W.
Abstract: Warmer and more persistent intrusions of Circumpolar Deep Water (CDW) onto the West Antarctic Peninsula are a key driver of the recent increase in ice shelf mass loss. The relatively warm and salty CDW is thought to be mixed up to the base of the ice shelves via shear‐driven turbulence where it has a high capacity to melt the ice. We analyze data from a year‐long mooring beneath George VI Ice Shelf at a location where double‐diffusive layering was observed. The turbulent dissipation rates do not vary with mean flow speed, suggesting shear‐driven mixing is not the driver of basal melt at this site. Instead, we predict the observed dissipation using a new method that links along‐isopycnal stirring of temperature anomalies with double‐diffusive convection. Our work suggests that along‐isopycnal temperature variance may be a stronger indicator of melt than flow speed within strongly stratified ice shelf‐ocean boundary layers. Plain Language Summary: Recently, warmer water has reached West Antarctic ice shelves (the floating extensions of the ice sheet), for longer periods, leading to an increased ice melt. Predicting how changing ocean conditions alter melting is key to understanding the response of the Antarctic ice sheet to global warming, which affects the extent of sea‐level rise. Basal melting is enhanced when warm and salty water is mixed up to the base of the ice. Often this mixing is forced by turbulence driven by the movement of water past the ice base. In this paper we analyze a year‐long mooring data set beneath George VI Ice Shelf and find that the measured turbulence does not correlate with the flow speed. We find instead that the turbulence can be explained by variations in temperature and salinity. These variations in temperature and salinity can create unstable density gradients due to the different rates of molecular diffusion between heat and salt, hence the name "double diffusion'. Unstable gradients in density can then force turbulence that mixes heat and salt up to the ice. If the mixing of heat and salt depends temperature and salinity variations rather than flow speed, it may affect predictions of ice melt. Key Points: Year‐long borehole mooring data in the George VI Ice Shelf ice‐ocean boundary layer are analyzed Observed dissipation rates do not vary with mean‐flow speed suggesting turbulence is not shear‐driven Double‐diffusive convection can explain the observed dissipation rates and melt rates, providing a route for parameterization